ONE OF THE LIMITROPHE TERRITORIES OF THE GLOBAL WORLD (Transformation of the States of the Baltic-Black Sea Region in the 21st Century) P a r t II - ZAZHIGAEV, Boris (CENTRAL ASIA AND THE CAUCASUS, 2009)
Early in the 21st century, the effects of the Soviet Union’s disintegration are only just starting to come to the fore, but I am convinced that the old-world order is already dead. Indeed, deprived of an external threat, the United States has been gradually losing its former role as global hegemon, while liberal democracy has proven unable to maintain its former Great Power status. The fear of the “red plague” in the East disappeared together with the Soviet Union; the old ideological bonds have slackened, while a new ideology is being formulated on the basis of particular interests. The political elite is still clinging to its imperial ambitions; however its social support is dwindling. The Americans are losing their former patriotic zeal: “Recent trends in public opinion suggest that the U.S. electorate is even less ready to sacrifice blood and treasure in foreign fields than it was during the Vietnam War.”1 America’s obsession with global domination died on the ruins of the bipolar system of international relations; the Soviet Union’s disintegration destroyed its “environment” and opened up wide vistas for the new rival geopolitical actors. The imperial U.S.-dominated global system of international relations of the past became a mirage before our eyes, while the milieu in which confrontation with the Soviet Union demanded concentrated efforts was replaced with the competitive environment of states of the same economic formation.2 Professor of Economic History at Harvard University Niall Ferguson has written in this connection: “We tend to assume that power, like nature, abhors a vacuum. In the history of world politics, it seems, someone is always the hegemon, or bidding to become it. Today, it is the United States; a century ago, it was the United Kingdom. Before that, it was France, Spain, and so on. The famed 19th-century German historian Leopold von Ranke, doyen of the study of statecraft, portrayed modern European history as an incessant struggle for mastery, in which a balance of power was possible only through recurrent conflict.